2017
DOI: 10.1186/s13063-017-1828-4
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of the Prostate cancer: Evidence of Exercise and Nutrition Trial (PrEvENT) dietary and physical activity modifications: a qualitative study

Abstract: BackgroundThere is increasing evidence that low levels of physical activity and diets low in fruit and vegetables and high in meat and dairy products are risk factors for prostate cancer disease progression. The Prostate cancer: Evidence of Exercise and Nutrition Trial (PrEvENT) aimed to assess a diet and physical activity intervention in men undergoing radical prostatectomy for localized prostate cancer. The trial included a qualitative component to explore the experiences of men participating in the trial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Important referents such as spouses, close friends or physicians, who are positive to the proposed changes may influence a person to perform the behaviour. This willingness to contribute to research has also been reported in previous qualitative studies among men with prostate cancer . The majority of the informants were married, and mentioned the support from their wives who engaged in the nutrition intervention and cooked appropriate food.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Important referents such as spouses, close friends or physicians, who are positive to the proposed changes may influence a person to perform the behaviour. This willingness to contribute to research has also been reported in previous qualitative studies among men with prostate cancer . The majority of the informants were married, and mentioned the support from their wives who engaged in the nutrition intervention and cooked appropriate food.…”
Section: Discussionsupporting
confidence: 73%
“…This willingness to contribute to research has also been reported in previous qualitative studies among men with prostate cancer. 3,5 The majority of the informants were married, and mentioned the support from their wives who engaged in the nutrition intervention and cooked appropriate food. Changing one's dietary habits during cancer treatment may be experienced as less strenuous when significant others are included to participate in dietary counselling in the clinic, and also in the research setting, as they can offer support and help with the planning and preparation of food.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wellestablished risk factors for PC are complex, including diet, physical activity, age, race/ethnicity, and a family history of the disease, etc. [3][4][5]. PC can be divided into the following three stages: localized stage, regional stage and distant stage [6].…”
mentioning
confidence: 99%